Life in the Trinity : an introduction to theology with the help of the church fathers - Fairbairn, Donald (Downers Grove, Illinois. IVP Academic., 2009)
What can the early church contribute to theology today? Although introductions to Christian theology often refer to its biblical foundations, seldom is much attention paid to the key insights the early church had into the nature of Christian faith and life. Donald Fairbairn takes us back to those biblical roots and to the central convictions of the early church, showing us what we have tended to overlook, especially in our understanding of God as Trinity, the person of Christ and the nature of our salvation as sharing in the Son's relationship to the Father. This book will prove useful to beginning theology students as well as advanced theologians who want to get at the heart of the Christian gospel.
Explanation of patristic citations -- Introduction: Getting started in Christian theology -- The heart of Christianity : the Son's relationship to the Father -- From the Father-Son relationship to the Trinity, and back -- Life as it was meant to be : a reflection of the Father-Son relationship -- What went wrong? : our loss of the Son's relationship to the Father -- The promise : God's preparation of the world for his Son -- The incarnation : the only Son becomes the firstborn Son -- Redemption : God's gift of his Son's relationship to the Father -- Becoming Christian : entering the Son's relationship to the Father -- Being Christian : another look at reflecting the Father-Son relationship.
Includes bibliographical references and indexes.
Keywords: Trinity -- History of doctrines -- Early church, ca. 30-600.